Reforming the Public Pension System in the Russian Federation - Eich, Frank (IMF Working Papers; Working Paper ;, 2012)
Pension reform is a key policy challenge in Russia. This paper examines how pension spending could increase in Russia in the absence of reforms, quantifies the impact of some recent proposals, and suggests some alternatives that would ensure public pension benefits - relative to wages - not fall from current levels while containing spending.